Kissing Nevus of Eyelid: A Rare Case Report: Poster Presentation - Case Report - Resident - dr. Silva Roza; Dr. dr. Hendriati Sp.M(K); dr. Mardijas Efendi Sp.M; Dr. dr. Ardizal Rahman Sp.M(K) (Majalah Oftalmologi Indonesia, 2023)
Introduction : Kissing nevus, also known as kissing mole, is a rare dermatological condition in the world and characterized by the presence of congenital nevi on both the upper and lower eyelids in symmetrical fashion. Additionally, this report highlights the treatment options available for patients with kissing nevus and discusses the importance of regular monitoring. Case Illustration : An 11-year-old female patient came with a complaint of a mole on the upper and lower eyelids since birth. The mole was felt to be getting bigger and starting to bother her. The patient feels insecure with the presence of this mole. The patient underwent nevus excision followed by retroauricular graft placement on the superior and inferior eyelidss. Then a biopsy showed benign nevus. After follow-up, it was found that the graft had grown and there was no necrotic tissue. Discussion : Kissing nevus is a rare skin condition that affects babies and young children. It is characterized by two identical birthmarks that appear on either side of the body, such as on the eyelids. Surgery involves removing the birthmarks surgically. Our patient underwent wide excision and palpebral reconstruction. Conclusion : Kissing nevuse is a unique skin condition marked by the presence of congenital nevi on both the upper and lower eyelids in a symmetrical pattern. It is worth noting that while treatment may be effective, there is a risk of scarring, infection, and other side effects associated with these procedures.